2013
DOI: 10.1007/s00774-013-0543-9
|View full text |Cite
|
Sign up to set email alerts
|

Risedronate improves bone architecture and strength faster than alendronate in ovariectomized rats on a low-calcium diet

Abstract: Clinical evidence suggests that, compared with alendronate, risedronate reduces fracture risk faster and more potently, with less bone mass gain. We tested the hypothesis that risedronate improves bone quality faster than alendronate using calcium-deficient, ovariectomized (OVX) rats. Female Sprague-Dawley rats at 24 weeks of age were divided into sham-operated and OVX groups and fed a low-calcium (0.05%) diet under paired feeding. After 12 weeks, OVX rats were divided into five groups and treated with vehicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…Both trabecular bone volume and mean density were shown to have decreased relative to sham in all three ovariectomized groups twenty-eight weeks following ovariectomy, while cortical bone abnormalities were not yet present, a result that also recapitulates previous findings of trabecular bone volume fraction and/or mineral density reductions without statistically significant changes in mineral density or area in ovariectomized relative to sham rats less than eight months following surgery [48, 49, 50], thus validating the establishment of pathology in our ovariectomized rats. Notably, some reversal in trabecular bone loss was apparent in the group treated with alendronate for fifteen weeks prior to measurement, as trabecular bone mineral density was higher in this group than water-treated ovariectomized controls, as well as the AP treatment group.…”
Section: Discussionsupporting
confidence: 79%
“…Both trabecular bone volume and mean density were shown to have decreased relative to sham in all three ovariectomized groups twenty-eight weeks following ovariectomy, while cortical bone abnormalities were not yet present, a result that also recapitulates previous findings of trabecular bone volume fraction and/or mineral density reductions without statistically significant changes in mineral density or area in ovariectomized relative to sham rats less than eight months following surgery [48, 49, 50], thus validating the establishment of pathology in our ovariectomized rats. Notably, some reversal in trabecular bone loss was apparent in the group treated with alendronate for fifteen weeks prior to measurement, as trabecular bone mineral density was higher in this group than water-treated ovariectomized controls, as well as the AP treatment group.…”
Section: Discussionsupporting
confidence: 79%
“…For example, a previous study demonstrated deeper penetration of RIS into the bone tissue compared to ALN [39]. And we have indeed demonstrated actual differences in the effects of RIS and ALN on micro architecture in calcium-deficient OVX rats [31]. Thus, in the context of post-TPTD therapy, it seems plausible that RIS exhibited a distinct effect from ALN on bone microstructure, most likely with complex interaction with residual effect of prior TPTD treatment.…”
Section: Discussionsupporting
confidence: 53%
“…Although these two bisphosphonates share the fundamental mechanism of inhibiting bone resorption [28], they significantly differ in potency of inhibiting farnesyl pyrophosphate synthase and affinity to hydroxyapatite [29]. Such unique properties may explain differences in clinical efficacy of the two bisphosphonates; despite its less prominent effect on bone turnover and BMD than ALN, RIS appears similarly to or even more effective in preventing hip and non-vertebral fractures during the first year of therapy [30] and in experimental animals as well under certain conditions [31]. As for sequential therapy, 1-year TPTD therapy after prior treatment with RIS or ALN for at least 2 years significantly increased BMD and bone formation markers, and the effect was greater in patients previously treated with RIS than in those pretreated with ALN [22].…”
Section: Introductionmentioning
confidence: 99%
“…[ 17 ] However, although there is no debate about the superiority of alendronate to risedronate in BMD gain at the trabecular bone, there is still debate about this superiority at the cortical bone. [ 18 ] Additionally, on the basis that the patient has a normal mechanical axis of the lower limb, the tension strain on the STLC of the femoral shaft is highest in the subtrochanteric area during the gait cycle. The strain is approximately 2,000 µε, which could cause a microcrack in the STLC during daily activities.…”
Section: Discussionmentioning
confidence: 99%